Career Counseling Interventions for International Students: A Comprehensive Analysis of Support Systems, Mental Health Challenges, and Professional Development Strategies - Betsi Siti Nurhidayah (P3M STAI Kuningan, 2025)
Background: International students face distinctive career development challenges compounded by mental health concerns and inadequate institutional support systems, yet career counseling interventions remain insufficiently tailored to their specialized needs.Objective: This study examined career counseling interventions for international students by analyzing support systems, mental health challenges, and professional development strategies to identify evidence-based practices for integrated service delivery.Method: A convergent parallel mixed-methods design was employed, involving 180 international students who completed quantitative surveys and 28 students and 14 practitioners who participated in qualitative interviews, supplemented by document analysis of 47 institutional materials.Findings and Implications: Findings revealed profound cultural misalignment between generic career services and international students' needs, with 65.6% of participants demonstrating poor psychological well-being and mental health serving as a partial mediator in relationships between institutional support and professional development competency. Peer networks functioned as compensatory support systems, while document analysis exposed substantial gaps between institutional diversity commitments and operational realities. The study advances theoretical frameworks by demonstrating career development and mental health as inseparable domains for international students, necessitating integrated intervention models.Conclusion: Systemic transformation of career counseling services is urgently needed to ensure equitable support that facilitates international students' professional integration and success in an increasingly interconnected global landscape.